An introduction to the law and economics of environmental policy issues in institutional design - Swanson, Timothy M. (Emerald, 2002)
An Introduction to the Law and Economics of Environmental Policy emphasises the importance of institutional design in addressing social problems. Three important issues concerning institutional design are: policies, instruments, and enforcement. This volume surveys each of the issues, and emphasises the common themes arising in optimal institutional design. These themes include the cost of complex institutional design, and the role of private institutions attaining social objects. This book will be particularly useful to law schools, departments of government, policy or economics, environmental managers and insurance companies.
Keywords: Institutional economics.; Environmental policy -- Economic aspects.; elektronické knihy; electronic books